Aspek Jiwa Tempat Sebagai Landasan Revitalisasi Kawasan (Studi Kasus: Perencanaan Perbelanjaan Kaki Lima di Kawasan Taman Sari Salatiga) - Harmilyanti Sulistyani (Ornamen, 2006)
Revitalisation is effort that reanimates an area. In case of Taman Sari area in Salatiga, revitalises done through change of function according to street vendor shopping centre with basic planning the spirit of place. Spirit of place (Genius Loci) is soul from place, representing Roman concept in effort to find the history root, cultural, and also character of place. To dig the spirit of place from non physical face (activity) can be done by using superimposes map, earn through history stemming explorations from literature and informant. Data result by verbal explorations must be accompanied with authentic data in map and photo form. The problem is realizing the street vendor shopping centre planning area with basis spirit of place to returning the area that be able to generator of commerce and recreation area. There are 3 problems lifted. First problem is appropriate revitalises area as same as the early function as town garden (open public space) by considering the spirit of place. The target is to increase area performance that representing commerce node in town. Second, revitalises in Taman Sari use street vendor shopping centre concept equipped by the supporter facility and area element that under colour by spirit of place. Third, place for street vendor and public space with basic spirit of place, processing the street furniture, skyline, the situation, colour element, and the green belt.Keyword: Revitalisation, Spirit of Place, Street Vendor Shopping Centre